Comparison of direct electrocaloric characterization methods exemplified by 0.92 Pb(Mg1/3Nb2/3)O3‐0.08 PbTiO3 multilayer ceramics. Issue 7 (30th March 2017) - Molin, Christian; Peräntie, Jani; Le Goupil, Florian; Weyland, Florian; Sanlialp, Mehmet; Stingelin, Natalie; Novak, Nikola; Lupascu, Doru C.; Gebhardt, Sylvia
Abstract: Electrocaloric device structures have been developed as multilayer ceramics (MLCs) based on fundamental research carried out on PMN‐8PT bulk ceramics. Two different MLC structures were prepared with nine layers each and layer thicknesses of 86 μm and 39 μm. The influence of the device design on its properties has been characterized by microstructural, dielectric, ferroelectric, and direct electrocaloric measurement. For direct characterization two different methods, ie temperature reading (thermistor and thermocouple) and heat flow measurement (differential scanning calorimetry), were used. A comparison of results revealed a highly satisfactory agreement between the different methods. This study confirms that MLCs are promising candidates for implementation into energy‐efficient electrocaloric cooling systems providing large refrigerant volume and high electrocaloric effect. Due to their micron‐sized active layers, they allow for the application of high electric fields under low operation voltages. We measured a maximum electrocaloric temperature change of Δ T =2.67 K under application/withdrawal of an electric field of Δ E =16 kV mm −1, which corresponds to operation voltages below 1.5 kV.